The role of Shaykh Abd Al-Ra'uf Al-Fansuri in the reconciliation of Sufism and Shari'ah of 17th century the Malay world - Muhamad Shukri, Abdul Salam; Arif, Ridwan (International Institute of Islamic Civilisation and Malay World (ISTAC), International Islamic University Malaysia (IIUM), 2018)
The tension between Sufism and sharīcah, i.e., the conflict of wujūdiyyah in Acheh in the 17th century had led Ṣūfī scholars, particularly cAbd al-Ra’ūf al-Fanṣūrī to seek the convergence between Sufism and sharīcah. Therefore, this study is carried out to examine the efforts of cAbd al-Ra’ūf to reconcile Sufism with sharīcah. It examines cAbd al-Ra’ūf’s approaches of reconciliation of Sufism and sharīcah in the general context as well as in the context of the controversial issue, i.e., the doctrine of waḥdat al-wujūd. It is a qualitative research which employs document analysis. The result of the study shows that cAbd al-Ra’ūf had played a significant role in reconciliating Sufism with sharīcah in 17th century Malay world. The approaches employed by cAbd al-Ra’ūf supported Sufism based on Qur’ān and Sunnah. They were also based on founding Sufism by orthodox (Sunnī) theology, emphasizing the significance of observance of practising sharīcah and integrating good conducts to Sufism. Meanwhile cAbd al-Ra’ūf’s approach of reconciliation in the controversial interpreted waḥdat al-wujūd in the orthodox sense and criticized the extreme approach in Islamic creed, i.e., passing judgement on Muslims as infidels.